Hypovitaminosis B12 is Associated with Long Term Consumption of Proton Pump Inhibitors (Medical Forum Monthly, 2024)
Objective: Determining vitamin B12 levels in subjects using Proton pump inhibitors (PPIs) for more than 3 years reporting at a tertiary care hospital of SindhStudy Design: Case control studyPlace and Duration: This study was conducted at the Department of Pathology and Biochemistry, Bilawal Medical College from January – December 2017.Materials and Methods: A sample of 100 subjects was selected; 50 cases using PPIs > 3 years duration and 50 controls (no PPIs) by convenient sampling through inclusion and exclusion criteria. 5 ml blood was collected; 3 ml put into EDTA tubes for complete blood counts and 2 ml for sera. Vitamin B12 was measured by ELISA assay. Results were analyzed on SPSS (ver 21.0) by Student t-test and Chi-square test at 95% CI (P ≤ 0.05).Results: Vitamin B12 in control and cases was found as 315.15±41.33 vs. 276.91±90.1 pg/dl (P=0.0001). Frequency and % of normal, borderline deficiency, deficiency and severe deficiency of vitamin B12 were noted as 31 (62%) vs. 11 (22%), 9(18%) vs. 21 (42%), 7 (14%) vs. 11 (22%), and 3 (6%) vs. 7 (14%) (P=0.0001). Cumulative vitamin B12 deficiency in 38% of control and 78% of cases (P=0.0001).Conclusion: In conclusion, the long term use of Proton pump inhibitor is associated with hypovitaminosis B12.